Case report: Placental chorioadenoma in a primiparous pug dog - Balogh, Orsolya; Diab, Santiago; Parker, Acadia; de Sousa, Gabriela C.; Cecere, Julie T.; McCarter, Samantha J.; Sponenberg, Dan Phillip (Frontiers in Veterinary Science, 2024)
A single 1.7 cm × 1.2 cm × 1 cm focal, raised, smooth, round, pink to flesh-colored mass protruding from the chorioallantois of the zonary placenta was found during Cesarean section in a primiparous pug bitch. Microscopically, the non-encapsulated, non-infiltrative, exophytic mass originated from the chorioallantoic stroma overlying the labyrinth and was composed of many arborizing fronds generally lined by 1 to 2 layers of cuboidal, columnar and occasionally polygonal, large trophoblastic cells, but frequently by a larger number of cells that occasionally piled up to form small nests or nodules. The gross and microscopic characteristics of this mass were compatible with a benign neoplastic process arising in the chorioallantois and involving placental trophoblasts, hence the diagnosis of a placental chorioadenoma. Five of the six newborn puppies were viable and of normal birthweight, while one puppy, which had lower birthweight than the others, could not be resuscitated and was humanely euthanized. Although placental tumors in dogs are very rare, this case is compelling evidence in the argument for routine inspection of canine placentas to identify potentially deleterious macro- or microscopic conditions that may be linked to negative fetal outcomes.